Joint Damage and Neuropathic Pain in Rats Treated With Lysophosphatidic Acid - McDougall, Jason J.; Reid, Allison R. (Frontiers in Immunology, 2022)
Joint pain is a complex phenomenon that involves multiple endogenous mediators and pathophysiological events. In addition to nociceptive and inflammatory pain, some patients report neuropathic-like pain symptoms. Examination of arthritic joints from humans and preclinical animal models have revealed axonal damage which is likely the source of the neuropathic pain. The mediators responsible for joint peripheral neuropathy are obscure, but lysophosphatidic acid (LPA) has emerged as a leading candidate target. In the present study, male and female Wistar rats received an intra-articular injection of LPA into the right knee and allowed to recover for 28 days. Joint pain was measured by von Frey hair algesiometry, while joint pathology was determined by scoring of histological sections. Both male and female rats showed comparable degenerative changes to the LPA-treated knee including chondrocyte death, focal bone erosion, and synovitis. Mechanical withdrawal thresholds decreased by 20-30% indicative of secondary allodynia in the affected limb; however, there was no significant difference in pain sensitivity between the sexes. Treatment of LPA animals with the neuropathic pain drug amitriptyline reduced joint pain for over 2 hours with no sex differences being observed. In summary, intra-articular injection of LPA causes joint degeneration and neuropathic pain thereby mimicking some of the characteristics of neuropathic osteoarthritis.